Answer:
x=-3 or x=-1
Step-by-step explanation:
Subtract 3 from both sides of your equation, it should look like this |3x+6|+3-3=6-3.
Simplify to get |3x+6|=3
Apply the absolute rule to get 3x+6=-3 or 3x+6=3.
3x+6=-3 : x=-3
3x+6=3 : x=-1
I'm glad I was able to help have a great day!
Answer:
14.4% decrease
Step-by-step explanation:
Here is the formula for finding the percentage of decrease:
(starting value - final value) / starting value * 100.
So for your question,
/
There was a 14.4% decrease within 50 years.
Answer:
Step-by-step explanation:
D. 18 1/5 +22 2/5 +40 1/5
-(-22 2/5) and -(-40 1/5) -----> -*- will become +
Answer:1/4
Step-by-step explanation:
1/2 is the same thing as 2/4 so.... 2/4 minus 1/4 is 1/4